Compact and low-proﬁle textile EBG-based antenna for wearable medical applications - Ashyap, Adel Y. I.; Zainal Abidin, Zuhairiah; Dahlan, Samsul Haimi; A. Majid, Huda; Mohd Shah, Shaharil; Kamarudin, Muhammad Ramlee; Alomainy, Akram (IEEE, 2017)
A compact wearable antenna with a novel miniatur-ized electromagnetic bandgap (EBG) structure at 2.4 GHz for med-ical application is presented in this letter. The design demonstrates a robust, compact, and low-proﬁle solution to meet the require-ments of wearable applications. The EBG structure reduces the back radiation and the impact of frequency detuning due to the high losses of human body. In addition, the structure improves the front-to-back ratio (FBR) by 15.5 dB. The proposed com-pact antenna with dimensions of 46 × 46 × 2.4 mm3 yields an impedance bandwidth of 27% (2.17–2.83 GHz), with a gain en-hancement of 7.8 dBi and more than 95% reduction in the speciﬁc absorption rate. Therefore, the antenna is a promising candidate for integration into wearable devices applied in various domains, speciﬁcally biomedical technology.